Ectodermal dysplasia: case report of aesthetic and functional rehabilitation - Di Lanaro, Nattália; Faker, Khawana; Paula, Viviane Andrade Cancio; Tostes, Mônica Almeida (Brazilian Dental Science, 2017)
Objective: The aim of this study is to report a case of aesthetic and prosthetic rehabilitation of a male 6-year-old patient diagnosed with Hipohidrotic Ectodermal Dysplasia, attended at the clinic of special patients held in the extension project of the Federal Fluminense University. Methods: This is a clinical, observational and descriptive study where the restorative and rehabilitative treatment was conducted and reported corresponding to the functional and aesthetic needs of the patient. Results: It was  realized the reconstruction of the anatomical shape of the teeth 51 and 61 and also was made a partial removable prosthesis to cover the absence of the teeth 71, 72, 74, 81 and 82, offering function, aesthetics and satisfaction reported by the patient. Conclusion: This case reports contributed to the increase of knowledge about the forms of Ectodermal Dysplasia on the importance of the differential diagnosis of the same, as well as to the teaching of the extension project of undergraduate students.